The effects of sorghum dried distillers grains with solubles on nursery pig performance - Sotak, K.M.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Two experiments were conducted to determine the effects of sorghum dried distillers grains with solubles (DDGS) on nursery pig growth performance. In both experiments, sorghum DDGS were added to corn- or sorghum-based diets to determine their impact on ADG, ADFI, and F/G. In Exp. 1, a total of 360 nursery barrows (PIC 1050, initially 15.1 lb and 26 d of age) were used with 5 pigs per pen and 9 pens per treatment. Pigs were allotted to 1 of 8 dietary treatments arranged in a 2 × 4 factorial with main effects of grain source (corn vs. sorghum) and sorghum DDGS (0, 15, 30, or 45%). Overall (d 0 to 34), pigs fed the corn and sorghum diets had similar ADG and ADFI; however, F/G was poorer (P < 0.05) for pigs fed the sorghum-based diets compared with the corn-based diets. Also, increasing DDGS reduced ADG (linear, P < 0.01) but increased ADFI (linear, P < 0.07), resulting in poorer F/G (linear, P < 0.01). In Exp. 2, a total of 180 nursery pigs (PIC 327 × 1050, initially 23.8 lb and 38 d of age) were used in a 21-d study with 6 pigs per pen and 5 pens per treatment. The dietary treatments were arranged in a 2 × 3 factorial with main effects of grain source (corn vs. sorghum) and DDGS (none, 30% corn DDGS, or 30% sorghum DDGS). Overall (d 0 to 21), no differences were found in ADG, ADFI, and F/G among pigs fed the corn- or sorghum-based diets. DDGS source (corn vs. sorghum) also did not influence growth performance; however, adding 30% DDGS to either the corn- or sorghum-based diets tended to reduce ADG (P < 0.10). Pigs fed diets with DDGS had similar ADFI and F/G when compared with pigs fed the basal diets (0% DDGS). In conclusion, sorghum can be used as a suitable replacement for corn in nursery diets. In Exp. 1, feed efficiency was approximately 5% poorer in pigs fed sorghum-based diets vs. pigs fed corn-based diets, which is similar to the energy content differences between the two grains. However, increasing sorghum DDGS to 45% of the diet reduced pig growth performance, so its inclusion needs to be evaluated on an income over feed costs basis.
Keywords: Swine; Corn; Corn DDGS; Sorghum; Sorghum DDGS; Nursery pig